Consumer Perception of the Halalness of Skincare Products: Case Study in Palangka Raya City - Nanda Putri; Erry Fitrya Primadhany; Ramadhani Alfin Habibie (LP2M IAIN Palopo, 2025)
This field research in Palangka Raya City revealed that consumer perceptions of the halalness of skincare products vary. Some consumers prioritize safety, skin suitability, and product popularity, while others are highly concerned with halalness as a form of religious observance and choose halal-certified products. The main factors influencing consumer choices are religious beliefs, the influence of family and friends, and the role of social media and influencers. Although halalness is not yet a priority for everyone, awareness of the importance of halal products continues to grow in the community. Data were collected through interviews with two consumers, two skincare sellers, and two religious scholars as informants. The aim was to understand the perceptions and factors influencing the choice of halal skincare products in Palangka Raya City. Semi-structured interviews were conducted directly with informants to freely express their views and experiences and obtain valid data regarding consumer perceptions and factors considered in choosing halal skincare products.